Advances in metal-organic framework-derived single-atom catalysts for biomedicine - Qiu, Li; Lin, Yingxi; Chen, Jun Song; Luo, Hong; Wu, Rui (Nano materials science, 2024)
As a alternative for natural enzymes, nanozymes has shown enzyme-like activity and selectivity in the field of various kinds of biomedical application, which has attracted considerable research interest. Recently, single-atom catalysts (SACs) have been extensively studied due to their similar active centers, coordination environment and better stability to natural enzymes. Metal-organic frameworks (MOFs) have been demonstrated as highly promising precursors for the synthesis of various types of SACs. MOF-derived SACs can not only significantly enhance the catalytic activity, but also improve the selectivity of nanozymes due to tunable coordination environment and structure, thereby receiving widespread attention in biomedicine. This review provided an overview of the preparation strategies for MOF-derived SACs, and then detailed the latest research progress of the SACs in the biomedical field for cancer, antibacterial, antioxidation and biosensors. Finally, the challenges and potential future opportunities of MOF-derived SACs in biomedical applications are proposed. [Display omitted]